Nematodes Associated with Two Species of Mentha (Lamiaceae) in Balochistan, Pakistan: Nematodes Associated Mentha (Biological Sciences - PJSIR, 2019)
Nematodes associated with Mentha spicata L. and Mentha longifolia L. were investigated in Balochistan in various localities so as to assess the variation in density of different nematode species found in the rhizosphere. Ten species of nematodes were found associated with Mentha spicata while four species were found in the rhizosphere of M. longifolia. Significant differences in nematode density were recorded (p at the most p < 0.01). The dominant nematodes associated with Mentha spicata were Pratylenchus projectus and Merlinius khuzdarensis while those associated with Menthe longifolia were Xiphinema americanum and Pratylenchus thornei.